House of Beth - Cullen, Kerry (Simon & Schuster, 2025)
"After a heart-wrenching breakup with her girlfriend and a shocking incident at her job, Cassie flees her life as an overworked assistant in New York for her hometown in New Jersey, along the Delaware. There, she reconnects with her high school best friend, Eli, now a widowed father of two. Their bond reignites, and within a few short months, Cassie is married to Eli, living in his house in the woods, homeschooling the kids, and getting to know her reserved neighbor, Joan. But Cassie's fresh start is less idyllic than she'd hoped. She grapples with harm OCD, her mind haunted by gory, graphic images. And she's afraid that she'll never measure up to Eli's late spouse, who was a committed homemaker and traditional wife. No matter what Cassie does, Beth's shadow still permeates every corner of their home. Soon, Cassie starts hearing a voice narrating the house's secrets. As she listens, the voice grows stronger, guiding Cassie down a path to uncover the truth about Beth's untimely death."--